Genomic selection and its research progress in aquaculture breeding - Hailiang Song; Tian Dong; Xiaoyu Yan; Wei Wang; Zhaohui Tian; Ai Sun; Ying Dong; Hua Zhu; Hongxia Hu (John wiley & Sons Australia, Ltd., 2025)
Since its introduction in 2001, genomic selection (GS) has progressed rapidly. As a research and application hot topic, GS has led to a revolution in the field of animal and plant breeding. Thanks to its ability to overcome the shortcomings of traditional breeding methods, GS has garnered increasing attention. Both theoretical and practical breeding studies have revealed the higher accuracy of GS than that of traditional breeding, which can accelerate genetic gain. In recent years, many GS studies have been conducted on aquaculture species, which have shown that GS produces higher prediction accuracy than traditional pedigree-based method. The present study reviews the principles and processes, preconditions, advantages, analytical methods and factors influencing GS as well as the progress of research in aquaculture into these aspects. Furthermore, future directions of GS in aquaculture are also discussed, which should expand its application to more aquaculture species.